2001
DOI: 10.1177/004051750107101107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound Treatment and Dye Crystalline Properties on Particle Size Distribution

Abstract: The influence of ultrasound on changes in dye particle size and the specific breakage rate of disperse dyes with different crystalline properties are investigated. The resultsshow that ultrasound breaks larger dye particles suspended in water in their insoluble form into finer dye particles and reduces the mean particle size of disperse dyes. The specific breakage rate for dye particles irradiated by ultrasound depends on their crystalline properties, and the breakage rate of a well crystallized dye is higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Finally, when the vapor density within the microbubbles increases, cavitation damage is reduced, owing to the inhibition of microbubble growth and collapse, and also to a decrease in the collapse velocities. This overall mechanism is called the cavitation thermodynamic effect [ 1, 3,5]. When the liquid temperature increases, the dissolved air content, the viscosity, and the surface tension decrease, while the vapor density within the microbubbles increases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, when the vapor density within the microbubbles increases, cavitation damage is reduced, owing to the inhibition of microbubble growth and collapse, and also to a decrease in the collapse velocities. This overall mechanism is called the cavitation thermodynamic effect [ 1, 3,5]. When the liquid temperature increases, the dissolved air content, the viscosity, and the surface tension decrease, while the vapor density within the microbubbles increases.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work we reported that breakage of dye particles by ultrasonication depends on their crystalline properties [5]. Despite this ultrasonication study, there has been no systematic investigation of the breakage of dye particles by ultrasound.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Unexpected and burst breakdown of these bubbles could create centralize high pressure, high temperature, and stun waves [1,2]. The influence of ultrasonic application on the dye adsorption can emphases in terms of regular diffusion of the dye molecules in the fluid, accelerating of the dispersion rate of dye within the composite and enhancing the reaction between composite and dye [3][4][5][6][7][8][9][10][11]. Recently, some attempts have been made to prepared and investigate novel nanocomposites for adsorption of some toxic materials.…”
mentioning
confidence: 99%
“…Figure 2 s ows the physical arrangement of the ultrasound bath in these experiments, which involved the ultrasound tr nsducer depicted in our previous paper [8].…”
mentioning
confidence: 99%